2000
DOI: 10.1177/00220345000790090701
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production and Bone Remodeling in Patients wearing Overdentures on Oral Implants

Abstract: The stability of titanium dental implants is determined by osseointegration. Bone is a dynamic tissue continuously remodeled through resorption and formation, processes controlled by local cytokine production. This study investigated osseotropic cytokine expression in gingival mucosa, in the intraforamina and inferior first molar zones, during rehabilitation with implant-retained overdentures. Specimens were taken from six patients prior to placement of implants in the intraforamina bone; at connection of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…In agreement with the study published by Schierano et al in which the pro-/anti-inflammatory cytokine levels were measured around titanium abutments (34), the findings of this study indicate no inflammatory response in the soft tissues ofthe implant analysed one, year after loading. The results of this study suggest a successful implant osseointegration (35). However, the expression of examined anti-inflammatory cytokines was higher around the zirconia abutment in comparison with the titanium abutment.…”
Section: (B)mentioning
confidence: 54%
“…In agreement with the study published by Schierano et al in which the pro-/anti-inflammatory cytokine levels were measured around titanium abutments (34), the findings of this study indicate no inflammatory response in the soft tissues ofthe implant analysed one, year after loading. The results of this study suggest a successful implant osseointegration (35). However, the expression of examined anti-inflammatory cytokines was higher around the zirconia abutment in comparison with the titanium abutment.…”
Section: (B)mentioning
confidence: 54%
“…Bone is a dynamic tissue continuously su�ject to remodeling through rea�sorption and formation, these processes �eing controlled �y the local production of cytokines, among other factors (4). Some of the studies in our review reported increased levels of IL-6, IL-8, IL-10 and IL-12 in periimplant disease, revealing their implication in the destruction of periimplant tissue and their usefulness as markers of periimplant disease (1,2,4, 7-9).…”
Section: Influence Of Interleukins 6 8 10 and 12 Upon Periimplant Imentioning
confidence: 81%
“…Some of the studies in our review reported increased levels of IL-6, IL-8, IL-10 and IL-12 in periimplant disease, revealing their implication in the destruction of periimplant tissue and their usefulness as markers of periimplant disease (1,2,4, 7-9). In contrast, other authors o�served no relationship �etween IL-6 and IL-10 levels and periimplant disease (2,7,8,10), discarding their implication in early dental implant loss (4). Regarding IL-6, Liskmann et al (1), on studying the levels of IL-6 in the crevicular fluid of the periimplant sulcus in 30 patients, recorded increased concentrations in patients with periimplant disease -a positive correlation �eing o�served with the clinical parameters (�leed-ing, pocket depth and gingival index).…”
Section: Influence Of Interleukins 6 8 10 and 12 Upon Periimplant Imentioning
confidence: 93%
See 2 more Smart Citations